BORDER MANAGEMENT AND PROCEDURE IN CASE OF HIGH LEVEL OF RADIATION AT THE BORDER CROSSINGS IN THE REPUBLIC OF NORTH MACEDONIA - Emilija Petrova; Metodija Dojcinovski (Revija za kriminologiju i krivično pravo)
The aim of this paper is to strengthen the ability of border crossing staff to check the presence of persons and vehicles for possible presence of radioactive materials outside regulatory control, in an effort to prevent smuggling and illicit trafficking in such means and materials. Regarding the use of radiation detection equipment, which is used at the border crossings in the Republic of North Macedonia, for the needs of control and verification of the entire import and export for possible presence of radioactive shipments. It documents the overall detailed process that the officers involved (customs officers and border police) will use to detect all radioactive material passing through the site, the process that will be used to determine the legitimacy of the radioactive substances that would be detected and the most appropriate way, which should be reacted and acted upon if illegal shipments of this type are detected. Information that will help existing and new officials to perform their duties in a timely manner, in an appropriate and consistent manner.